Looking for coeliac disease in children with type 1 diabetes mellitus. (7th July 2014) - Porter, Jody A; MacKenzie, Karen; Darlow, Brian; Day, Andrew S
<x xml:space="preserve">Abstract</x> Aim To establish how clinicians in New Zealand (NZ) approach screening for and management of coeliac disease (CD) in type 1 diabetes mellitus (T1DM) in their paediatric patients. Methods All clinicians caring for children under 15 years with T1DM in NZ in 2010 were asked to complete an online survey detailing their personal and departmental approach to diagnosing and managing patients with CD and T1DM. Results Thirty‐four from 37 clinicians responded to the survey. Most clinicians in NZ have a protocol for screening for CD in T1DM, and 25/34 respondents will screen for CD at diagnosis of T1DM. Those who do not screen will use symptoms, growth and hypoglycaemia as indicators to test. All use anti‐tissue transglutaminase to screen for CD, and 32/34 use biopsy‐proven CD as a criterion for commencing gluten‐free diet (GFD). Nearly all consultants will still advise a GFD in symptom‐free CD and will try to encourage the patients to adopt a GFD if they initially decline. Conclusions Most clinicians in NZ screen for CD, but there is a wide variation in practice.